The policy relevance of personality traits - Bleidorn, Wiebke; Hill, Patrick L.; Back, Mitja D.; Denissen, Jaap JA; Hennecke, Marie; Hopwood, Christopher J.; Jokela, Markus; Kandler, Christian; Lucas, Richard E.; Luhmann, Maike; Orth, Ulrich; Wagner, Jenny; et al. (The American psychologist, 2019)
Personality traits are powerful predictors of outcomes in the domains of education, work, relationships, health, and well-being. The recognized importance of personality traits has raised questions about their policy relevance, that is, their potential to inform policy actions designed to improve human welfare. Traditionally, the use of personality traits in applied settings has been predicated on their ability to predict valued outcomes, typically under the assumption that traits are functionally unchanging. This assumption, however, is both untrue and a limiting factor on using personality traits more widely in applied settings. In this article, we present the case that traits can serve both as relatively stable predictors of success and actionable targets for policy changes and interventions. Though trait change will likely prove a more difficult target than typical targets in applied interventions, it also may be a more fruitful one given the variety of life domains affected by personality traits. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Gesehen am 04.03.2020